2015
DOI: 10.1161/strokeaha.115.009779
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Intra-Arterial Treatment as an Adjunct to Intravenous Tissue-Type Plasminogen Activator for Acute Ischemic Stroke

Abstract: Background and Purpose The objective of this study was to determine the cost-effectiveness of intraarterial treatment within the 0- to 6- hour window after intravenous (IV) tissue plasminogen activator (tPA) within 0- to 4.5-hours compared to IV tPA alone, in the US setting and from a social perspective. Methods A decision analytic model estimated the lifetime costs and outcomes associated with the additional benefit of intraarterial therapy compared to standard treatment with IV tPA alone. Model inputs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 29 publications
4
77
0
5
Order By: Relevance
“…This is concordant with the large clinical effect size observed in the randomized trials, and sensitivity analyses suggested that these findings are robust to a range of assumptions. Our findings were consistent with the most recent published economic evaluation from the United States, 22 which evaluated new-generation devices and used efficacy estimates from a single *This study 31 did not find a significant difference in mortality between groups (28.8% mRS 6 in the endovascular treatment group v. 34% in the IT group). Therefore, we assumed no survival benefit for MT in this scenario analysis.…”
Section: Discussionsupporting
confidence: 90%
“…This is concordant with the large clinical effect size observed in the randomized trials, and sensitivity analyses suggested that these findings are robust to a range of assumptions. Our findings were consistent with the most recent published economic evaluation from the United States, 22 which evaluated new-generation devices and used efficacy estimates from a single *This study 31 did not find a significant difference in mortality between groups (28.8% mRS 6 in the endovascular treatment group v. 34% in the IT group). Therefore, we assumed no survival benefit for MT in this scenario analysis.…”
Section: Discussionsupporting
confidence: 90%
“…The acute management costs for IAT usually increases the standard costs required for IVT, given the expensive devices used and expert personnel required to perform the IAT (Ganesalingam et al., 2015; Leppert et al., 2015). However, these high costs may be considered acceptable given the incremental lifetime cost‐effectiveness ratio of IAT costs remained within a willingness to pay threshold of ≤$50,000/QALY (Ganesalingam et al., 2015; Leppert et al., 2015). We here separately compared the costs of acute IAT management and those of long‐term institutional rehabilitation after IAT.…”
Section: Discussionmentioning
confidence: 99%
“…While IAT is more expensive and requires specialized personnel, its high cost is justified by the improved lifetime clinical outcomes and cost‐effectiveness (Aronsson, Persson, Blomstrand, Wester, & Levin, 2016; Ganesalingam et al., 2015; Leppert, Campbell, Simpson, & Burke, 2015). However, the long‐term (>3 months post‐IAT) clinical and cost benefits for patients stratified according to the time from symptom onset to recanalization remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several cost utility and cost effectiveness analyses have suggested that although EVT is a costly procedure it is likely to be cost effective [31][32][33].…”
Section: Meta-analyses Of Trialsmentioning
confidence: 99%